INCREASING THE MANAGERIAL CAPACITY OF THE BUMDESA HEAD IN TAMANSARI DISTRICT THROUGH THE BUMDESA SCHOOL AND CLINIC - Herman Herman; Ferdisar Ferdisar; Abdul Kohar (Rural Development For Economic Resilience (RUDENCE), 2022)
This Community Service (PKM) aims to increase the capacity and ability of the head of BUMDesa in Tamansari District in improving the development of BUMDesa in Tamansari District, Bogor Regency. This problem started from the undeveloped BUMDes in Tamansari District. Of the 8 villages in Tamansari sub-district, all of them have established BUMDesa, but only two BUMDesa have active status, the remaining seven BUMDesa are inactive. The failure of the seven BUMDesa in Tamansari Sub-district was influenced by many factors, one of which was the weak capacity and ability of the Head of BUMDesa. This is because the elected head of BUMDesa does not have adequate knowledge, experience and education. On this basis, this service is carried out in the form of providing continuous managerial training in the form of BUMDesa schools and clinics for BUMDes heads in Tamansari District, Bogor Regency. The outputs resulting from this activity are in the form of increasing the ability and capacity of the Head of BUMDesa in Tamansari District, the creation of professional and competitive BUMDesa.